If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 1 = 12x + -11 Reorder the terms: 1 + 13x = 12x + -11 Reorder the terms: 1 + 13x = -11 + 12x Solving 1 + 13x = -11 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 1 + 13x + -12x = -11 + 12x + -12x Combine like terms: 13x + -12x = 1x 1 + 1x = -11 + 12x + -12x Combine like terms: 12x + -12x = 0 1 + 1x = -11 + 0 1 + 1x = -11 Add '-1' to each side of the equation. 1 + -1 + 1x = -11 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = -11 + -1 1x = -11 + -1 Combine like terms: -11 + -1 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| h(9)=-27 | | 2.5/13=45 | | 17a^5-7a^3-19a^5+18a^3= | | 9(x+4)+2=11x-2(x-4) | | 7(9+4f)=-27 | | -3x+10=6x+1 | | 6.8x=-0.2244 | | 5/8x-11=14 | | 9.25+8=15.5+13 | | 0=-.2x^2+16x | | -(x+2)=4x-2 | | 1/4=1/9z | | y=-.2x^2+16x | | 31.4=3.14r | | .66x=5 | | 20x-40=10x-70 | | 6(x+3)-(x-7)= | | 2=.57x | | x+4.4=8.2 | | 0=-16x^2+64x+32 | | 3x+(12.8+x)=200.3 | | 15x-6=-2x-10 | | 4p-(9p+13)=6-(7p-8) | | 2567636.50+615493x=(3*648043)+648043x | | 30x+25=60x+25 | | .375x=5 | | -3+5-4x=2x+4-5x | | 24x-17x=13x-15 | | 3y-(9y+8)=7-(12y-4) | | 9(x+5)=3(x+9) | | x(x+2)(x+4)(x+6)=9 | | 11x-6x+180=11x+96 |